2011
DOI: 10.1155/2011/625939
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Oxidized Low-Density Lipoprotein Is an Independent Risk Factor in Young Patients with Coronary Artery Disease

Abstract: Objectives: Oxidized low-density lipoprotein (ox-LDL) is considered to be a key factor of initiating and accelerating atherosclerosis. The objective of this study was to investigate the role of ox-LDL in young patients with coronary artery disease (CAD). Methods: 128 consecutive angiographically proven young CAD patients (aged ≤ 55 years) were enrolled, and 132 age-matched non-CAD individuals (coronary angiography normal or negative finding by coronary ultrafast CT) were set as control group. Conventional risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 23 publications
2
24
0
1
Order By: Relevance
“…22,23 There is increasing evidence suggest that oxidative modification of LDL plays a pivotal role in the development of atherosclerosis. [24][25][26][27] This study found that the levels of ox-LDL were significantly higher in ACS cases than in healthy control group, which was similar to our previous findings. 26,27 These finding agree with the study mad by who found that Huiling Huang et al 28 These findings indicate that serum ox-LDL levels are closely related with CAD.…”
Section: Discussionsupporting
confidence: 91%
“…22,23 There is increasing evidence suggest that oxidative modification of LDL plays a pivotal role in the development of atherosclerosis. [24][25][26][27] This study found that the levels of ox-LDL were significantly higher in ACS cases than in healthy control group, which was similar to our previous findings. 26,27 These finding agree with the study mad by who found that Huiling Huang et al 28 These findings indicate that serum ox-LDL levels are closely related with CAD.…”
Section: Discussionsupporting
confidence: 91%
“…However (and even taking into account that our study did not focus on imagiological analysis), our data draw attention to the importance of measuring new markers of dyslipidemia (particularly Ox-LDL and small HDL), more reliably related with the disease and its progression, continuing to support the working hypothesis of thinking that the proinflammatory and thrombogenic mechanisms associated with an abnormal lipid profile could contribute to MS progression, through diverse processes at the BBB vascular endothelium. The relevance of "non-classic" markers of cardiovascular risk, such as oxidized LDL, has been increasingly demonstrated in young or adult subjects with coronary artery disease [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…7 Apart from metabolic alterations, abnormal oxidation of LDL is an important step in initiation and progression of atherosclerosis. 8 Recent research suggests that oxidized low-density lipoprotein (oxLDL) levels are increased in patients with coronary atherosclerosis 8 and PAD. 9 Recently, it has been shown that oxLDL is independently associated with 10-year risk of CAD events and improves the reclassification capacity of Framingham-derived risk functions.…”
Section: Introductionmentioning
confidence: 99%